2007
DOI: 10.5194/acp-7-3153-2007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diurnal variations of air traffic on contrail radiative forcing

Abstract: Abstract. We combined high resolution aircraft flight data from the EU Fifth Framework Programme project AERO2k with analysis data from the ECMWF's integrated forecast system to calculate diurnally resolved 3-D contrail cover. We scaled the contrail cover in order to match observational data for the Bakan area (eastern-Atlantic/western-Europe).We found that less than 40% of the global distance travelled by aircraft is due to flights during local night time. Yet, due to the cancellation of shortwave and longwav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 29 publications
7
78
4
Order By: Relevance
“…One such a region is the western Europe area of 10°W to 23°E and 40°N to 56°N from Meyer et al [2002], where data of the Advanced Very High Resolution Radiometer (AVHRR) sensor onboard the NOAA 14 satellite was analyzed for the 1995-1997 period using an operational contrail detection algorithm. The 1985 average contrail coverage for this region reported by Meyer et al [2002] is 0.5%, while Bakan et al [1994] and Stuber and Forster [2007] reported values of approximately 0.7% and 0.9%, respectively. Our value for the same region is 0.97% for the year 1985.…”
Section: Contrail Coveragementioning
confidence: 94%
See 4 more Smart Citations
“…One such a region is the western Europe area of 10°W to 23°E and 40°N to 56°N from Meyer et al [2002], where data of the Advanced Very High Resolution Radiometer (AVHRR) sensor onboard the NOAA 14 satellite was analyzed for the 1995-1997 period using an operational contrail detection algorithm. The 1985 average contrail coverage for this region reported by Meyer et al [2002] is 0.5%, while Bakan et al [1994] and Stuber and Forster [2007] reported values of approximately 0.7% and 0.9%, respectively. Our value for the same region is 0.97% for the year 1985.…”
Section: Contrail Coveragementioning
confidence: 94%
“…This is caused by the fact that the contrail formation is affected by two independent factors, one being the amount of air traffic, and the other one being the ambient meteorological conditions. Thus, if the winter months correspond to low air traffic (with a minimum in December) and the summer months correspond to high air traffic (with a maximum in August), the meteorological conditions are less favorable to contrail formation in the three summer months, mainly because in these months the northern hemisphere midlatitudes upper troposphere relative humidity reaches its minimum [Marquart et al, 2004;Stuber and Forster, 2007]. The combination of these two independent factors results in the largest global monthly mean contrail coverages being recorded in June and October.…”
Section: Contrail Coveragementioning
confidence: 99%
See 3 more Smart Citations